Comparison of Odontogenic Space Infection in Diabetic and Non-Diabetic Patients - Haroon, Asif Nazir Ch., Fahad Khaliq, Husna Shams, Wajeeha Chauhdry, Waqar Hussan Kulachi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aimed to assess and compare the etiology; odontogenic spaces involved, and associated complications between diabetic and non-diabetic patients. Methodology: A cross-sectional study was conducted at the Nishtar Institute of Dentistry, Multan, between October 2021 and March 2022. The study population included 37 participants selected through consecutive non-probability sampling. Eligible participants were individuals of both sexes, aged 18 to 60, with an odontogenic infection. Exclusion criteria comprised localized dental abscesses without fascial space involvement, infections unrelated to odontogenic origin, and unwillingness to participate. Data on demographic characteristics and clinical findings were collected using a self-structured questionnaire. Statistical analysis was performed using SPSS version 20.0, calculating the mean, standard deviation, frequency, and percentages. Statistical significance was set at p < 0.05. Results: The study enrolled 37 patients diagnosed with odontogenic maxillofacial space infections. Among them, 15 (40.5%) were female, and 22 (59.5%) were male, with a mean age of 31.51 years (SD 9.642). Of the participants, 23 (62.2%) had diabetes, while 14 (37.8%) were non-diabetic. Conclusion: The results of this research suggest that diabetic patients are more susceptible to odontogenic infections, specifically dental caries. Additionally, diabetic patients demonstrated a higher prevalence of multiple involved spaces and an increased likelihood of developing complications. Keywords: odontogenic infection, diabetes mellitus, odontogenic space, complications